Long-term financing needs for HIV control in sub-Saharan Africa in 2015-2050: a modelling study - Atun, Rifat A.; Bärnighausen, Till (BMJ open, 2016)
Objectives: To estimate the present value of current and future funding needed for HIV treatment and prevention in 9 sub-Saharan African (SSA) countries that account for 70% of HIV burden in Africa under different scenarios of intervention scale-up. To analyse the gaps between current expenditures and funding obligation, and discuss the policy implications of future financing needs. Design: We used the Goals module from Spectrum, and applied the most up-to-date cost and coverage data to provide a range of estimates for future financing obligations. The four different scale-up scenarios vary by treatment initiation threshold and service coverage level. We compared the model projections to current domestic and international financial sources available in selected SSA countries. Results: In the 9 SSA countries, the estimated resources required for HIV prevention and treatment in 2015-2050 range from US$98 billion to maintain current coverage levels for treatment and prevention with eligibility for treatment initiation at CD4 count of <500/mm3 to US$261 billion if treatment were to be extended to all HIV-positive individuals and prevention scaled up. With the addition of new funding obligations for HIV—which arise implicitly through commitment to achieve higher than current treatment coverage levels—overall financial obligations (sum of debt levels and the present value of the stock of future HIV funding obligations) would rise substantially. Conclusions: Investing upfront in scale-up of HIV services to achieve high coverage levels will reduce HIV incidence, prevention and future treatment expenditures by realising long-term preventive effects of ART to reduce HIV transmission. Future obligations are too substantial for most SSA countries to be met from domestic sources alone. New sources of funding, in addition to domestic sources, include innovative financing. Debt sustainability for sustained HIV response is an urgent imperative for affected countries and donors.